SEMAGLUTIDE IN THE TREATMENT OF OBESITY- A NEW LOOK AT AN EFFECTIVE PHARMACOLOGICAL TOOL IN THE FIGHT AGAINST EXCESSIVE BODY WEIGHT - Monika Rogowska; Paulina Lewaśkiewicz; Karolina Wojdat-Krupa; Paweł Babiński; Filip Lachowski (International Journal of Innovative Technologies in Social Science, 2026)
Obesity is a chronic and progressive disease, the prevalence of which continues to rise worldwide, leading to a worsening quality of life, increased incidence of other diseases, and mortality. Treating obesity poses many challenges in daily clinical practice, therefore requiring a comprehensive medical approach that involves not only lifestyle changes but also pharmacotherapy and the use of bariatric surgery methods. Due to the ongoing exploration of obesity-related issues, therapy with semaglutide, belonging to the glucagon-like peptide-1 (GLP-1) receptor agonist class, has gained popularity, recently approved for treating obesity. Numerous clinical studies and observations have demonstrated that semaglutide has the most significant impact on weight loss among all drugs used in obesity therapy, accompanied by improvements in quality of life and cardiovascular risk factors. The aim of this article is to present the current state of knowledge regarding the use of semaglutide in obesity therapy, its safety, and its correlation with other obesity treatment methods. In this article, we used English databases such as PubMed, Google Scholar and Medline. We selected articles based on keywords such as semaglutide, glucagon-like peptide –1, obesity treatment, weight loss.